"That's How She Talks": Animating Text Message Evidence in the Sexual Assault Trial. Issue 2 (11th May 2018) - Hlavka, Heather R.; Mulla, Sameena
Abstract : This ethnographic study of criminal sexual assault adjudication shows how prosecutors, defense attorneys, and witnesses animate text message evidence. In contrast to other forms of courtroom testimony, text messages function as multiauthored representations of recorded correspondence in the past. Attorneys and witnesses animate texts authored by or said to characterize persons represented at trial. By whom and how the texts are animated shapes trial processes. Through a detailed comparative case analysis of two Milwaukee, WI, sexual assault trials, this article attends to the process by which text messages are said to personify or characterize authors' meaning and intent. This animation of electronically transmitted text speaks to credibility and variably emphasizes a witness's place within gendered and racialized cultural norms. Rather than unsettling the trope of "he said, she said, " text messages become contested evidence animated by court actors within contexts of long‐standing cultural narratives of sexual victimization and offending.